Advancing anatomy teaching by incorporating the neurophysiological concepts of learning - Vijaya Kumar Konuri; Abu Ubaida Siddiqui (Wolters Kluwer Medknow Publications, 2021)
Gross anatomy is staring at a challenge either to transform or to disappear, if not as a science may be as a faculty, in the present era of ever-evolving medical education systems. It is a well-understood fact that retention of anatomical information is not an easy job. It is also worthwhile to mention here that technology is a great contributor in the elaborate process of teaching and learning, but a logical methodology for delivering knowledge must gain precedence over any means of technology. A scientific approach in the acquisition of knowledge shall always enhance the sensory input in the brains of the learners. The knowledge disseminated should be delivered for a larger purpose to make it useful for the humankind. The scientific methodology of knowledge acquisition implies that documented sensory input shall not be automatically converted into a repertory of facts and figures. To make the process interesting and active, the need of the hour is to develop ordered arrays of data deliverance. All modalities of scientific teaching should move ahead through interconnected phases of knowledge. The delivery of sheer facts as a description is many a times entering the brain as a mere theoretical fact with not deductive results. The accumulated facts need to be correlated with the various facts that are being thrown open by the relevant other branches to discern the underlying patterns. Each organ is to a great extent the product of the function it performs, in the present as well as in the past. We have tried to summarize the above concept, thus trying to establish the fact that "the structure is a function in space and function is a structure in time." The neuroanatomic-physiologic approaches should play the leading role in the development of the concepts of learning of anatomy.